Phase retrieval of ultrashort laser pulses using a MIIPS algorithm - Comin, Alberto; Ciesielski, Richard; Coca-López, Nicolás; Hartschuh, Achim (Optics express, 2016)
We developed a new method for retrieving the group delay dispersion of a laser from Multiphoton Intra-pulse Interference Phase Scan (MIIPS) data. The method takes into account the spectral amplitude of the laser pulse and provides a direct feedback on the accuracy of the retrieval. The main advantage of the method derives from providing sufficiently high accuracy to avoid the need for multiple experimental iterations. Another advantage is that the new method can discriminate among pulses with different spectral phase and amplitude profiles, in which MIIPS traces occupy the same position in the phase-frequency MIIPS map.